In vivo toxicity studies of fusarium mycotoxins in the last decade: A review. (April 2015) - Escrivá, L.; Font, G.; Manyes, L.
Highlights: A compilation of in vivo studies about Fusarium mycotoxins in the last decade was performed. The main Fusarium mycotoxins studied were identified. The in vivo assays were classified regarding the proposed objective. Aspects such as animal species, doses, application routine, exposure time, and results obtained were analyzed. Abstract: This review summarizes the information regarding the in vivo studies of Fusarium mycotoxins in the last decade. The most common studies are classified as subacute toxicity, subchronic toxicity, acute toxicity, toxicokinetic studies and teratogenicity in order of importance. The most used animals in in vivo studies are pigs, rats, chickens and mice. Fumonisin B1, deoxynivalenol, zearalenone, nivalenol and T-2 toxin are the most studied fusarotoxins. Studies with combinations of mycotoxins are also frequent, deoxynivalenol generally being one of them. The predominant route of administration is oral, administered mostly in the form of naturally contaminated feed. Other administration routes also used are intraperitoneal, intravenous and subcutaneous. In vivo research on Fusarium mycotoxins has increased since 2010 highlighting the need for such studies in the field of food and feed safety.